2017
DOI: 10.1038/s41598-017-03014-2
|View full text |Cite|
|
Sign up to set email alerts
|

One-month spaceflight compromises the bone microstructure, tissue-level mechanical properties, osteocyte survival and lacunae volume in mature mice skeletons

Abstract: The weightless environment during spaceflight induces site-specific bone loss. The 30-day Bion-M1 mission offered a unique opportunity to characterize the skeletal changes after spaceflight and an 8-day recovery period in mature male C57/BL6 mice. In the femur metaphysis, spaceflight decreased the trabecular bone volume (−64% vs. Habitat Control), dramatically increased the bone resorption (+140% vs. Habitat Control) and induced marrow adiposity invasion. At the diaphysis, cortical thinning associated with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
111
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 53 publications
8
111
1
1
Order By: Relevance
“…After the 1‐month BION‐M1 mission in 2013, we evidenced a dramatic increase in empty osteocyte lacunae in mouse skeletons, suggesting osteocyte death . Osteocytes orchestrate bone resorption and formation activities through the production of cytokines, including osteoclastogenic and osteoblastic signaling proteins (such as sclerostin and periostin), the two activities balancing directly at the remodeling site .…”
Section: Discussionmentioning
confidence: 94%
“…After the 1‐month BION‐M1 mission in 2013, we evidenced a dramatic increase in empty osteocyte lacunae in mouse skeletons, suggesting osteocyte death . Osteocytes orchestrate bone resorption and formation activities through the production of cytokines, including osteoclastogenic and osteoblastic signaling proteins (such as sclerostin and periostin), the two activities balancing directly at the remodeling site .…”
Section: Discussionmentioning
confidence: 94%
“…There also have been a limited number of long duration (>3 wk), rodent spaceflight experiments. A recent unmanned, Russian biosatellite experiment (Bion M1) that entailed sample recovery after return to Earth revealed that 30 days of spaceflight caused muscle, thymus and spleen atrophy ( 4,5 deficits in structure of various skeletal elements ( 6,7 ), altered structural morphology and changes in gene expression of several tissues 5,8 . The lengthy interval (13 hr) between capsule reentry and sample recovery for the Bion M1 mission may have affected at least some of these findings.…”
mentioning
confidence: 99%
“…In support of the reduction of immune cell development, it was previously shown that Bion-M1 flight induced a 64% reduction in femur trabecular volume of the same mice, which was not restored by the recovery period (26), and that their ankle bone volume loss is aggravated after 1 wk of reambulation on Earth (27). From our previous studies showing that 21 d of HU causes bone remodeling and a concomitant decrease in B lymphocyte maturation in the bone marrow of the same mouse strain (15), we expected that immune cell development would already be affected at landing because it has been established that spaceflight induces bone loss (28); however, this was not the case.…”
Section: Discussionmentioning
confidence: 88%
“…This could be due to differences in bone alteration kinetics between HU and real spaceflight, or the age of animals because HU mice (15) were younger (3 mo) than Bion-M1 mice. Impaired B lymphopoiesis could also result from differences in the imbalance between bone formation and resorption because it has been shown that bone loss results from reduced bone formation during HU (29) and from increased osteoclastic resorption during spaceflight (26). Despite this remark, however, these 2 studies clearly demonstrate that spaceflight conditions have a negative effect on B lymphopoiesis.…”
Section: Discussionmentioning
confidence: 89%